Inter-relationships among erodibility, soil tolerance and pysical-chemical attributes in northwestern of São Paulo state - Lima, César G. R. [UNESP]; Marques, Sâmia M. [UNESP]; Lollo, José A. [UNESP]; Costa, Nídia R. [UNESP]; Carvalho, Morel P. [UNESP] (Journal of Urban and Environmental Engineering, 2019)
Erosive processes are major environmental problems for soil and constitute a great conservation planning challenge. Knowledge of erodibility and soil loss tolerance, as well as their interactions with the physical and chemical attributes of soil, may allow important diagnostics for sustainable management. More dexterous processes for obtaining such information can be very interesting solutions in large areas with strong climatic and environmental dynamics. The aim of this study was to determine soil erodibility (K) and soil loss tolerance (T) for 32 kinds of soil in the northwestern region of São Paulo State from indirect methods and to assess their linear and spatial correlations with soil physical-chemical attributes. The evaluated attributes were: textural relationship (TR), particle density (PD), bulk density (BD), total porosity (TP), macroporosity (MA), microporosity (MI), water capacity storage (WCS), organic matter (OM) and soil pH (pH). The results showed that the K factor ranged from 0.0094 to 0.0758 Mg ha h/ha MJ mm (surface depth), while T values ranged from 3.09 to 14.79 Mg/ha year. The erodibility and loss tolerance presented significant interactions with the physical and chemical soil attributes, especially WCS and TR which showed the best regression adjustments. From a geostatistical point of view, the erodibility and soil loss tolerance also showed considerable spatial correlations with most soil physical properties (especially interactions with the TP and TR), allowing for the best maps using the cokriging technique. This allowed us to conclude that the adopted simple and relatively low-cost approach was effective in obtaining K and T, showing its potential for implementation in large areas without complex surveys, in situ tests, and long term climate data series, which is a common situation in large areas in less developed countries.
Keywords: Geostatistics; Soil conservation; Soil erosion; Sustainable management